KITAB YUDIT: KEMENANGAN KAUM PEREMPUAN ATAS KAUM LAKI-LAKI? - Hadianto, Jarot (Jurnal Orientasi Baru, 2015)
The story of Judith seems less convenient for Scripture readers today. Judith, an ordinary Israeli widow, uses her beauty to establish herself in the camp of the Assyrian army. She deceives and lies to them. She then puts the commander of the Assyrian army into her deadly trap and kills him in his total unconsciousness. Should we call those heroic deeds? Does Judith deserve to be called a heroine? Moreover, despite the fact that Judith’s courage is praised, there are some verses in the book of Judith which are oppressive to women, including to Judith herself. These verses emphasize the negative attitudes held by the Israelite society toward women.